Blood Pressure Monitoring System Using Mamdani Fuzzy Logic Method Based on Microcontroller - Nurhasanah Tambunan; Sriani Sriani (SAINTIS Publishing, 2025)
Health is a vital aspect that must be continuously monitored, one of which is through blood pressure measurement. In general, blood pressure measurement is carried out using a manual sphygmomanometer that requires medical expertise, so the results are often not well documented. This study aims to design and implement a blood pressure monitoring system based on a microcontroller using the Mamdani fuzzy logic method. The system is developed by integrating a digital blood pressure sensor and a MAX30100 heart rate sensor connected to an Arduino Uno. The Mamdani fuzzy method is employed to classify the measurement results into three categories: hypotension, normal, and hypertension, based on systolic, diastolic, and heart rate (BPM) values. The system is also equipped with an LCD as a visual indicator to display the user’s health condition in real time, quickly, and informatively. Experimental results show that the system can operate properly, achieving an average error rate of 3.44% and an accuracy level of 96.28%. These findings indicate that the proposed monitoring system is sufficiently accurate, flexible in handling uncertain biological data, and has great potential to be developed as an initial screening tool for health conditions, particularly at home or in areas with limited access to medical facilities.